(untitled) (Research, Society and Development, 2020)
Non-stoichiometric hydroxyapatite (HAp) presents an additional phase in its structure due to calcium or phosphorus excess, which can influence the material’s mechanical properties, as well as its bioactivity and biodegradability. While stoichiometric HAp, with calcium to phosphorus ratio (Ca/P) of 1.67, has been widely investigated, only a few studies have reported the synthesis of HAp with higher Ca/P ratio. In this work, non-stoichiometric HAp nanoparticles were synthesized using chemical precipitation method followed by a calcination protocol. In order to achieve better process control with chemical precipitation, starch, a natural additive, was applied. Three types of starch were selected for comparison: nonionic starch (NS), soluble starch (SS), and cationic starch (CS). Infrared spectroscopy and chemical analysis results confirmed the non-stoichiometric profile of the synthesized HAp, with a 1.98 Ca/P ratio. X-ray diffraction (XRD) results showed that HAp and calcium oxide (CaO) crystalline phases were obtained and no residual starch was detected. Rietveld refinements confirmed that, for all three types of starch, the content of crystalline HAp was greater than 96.5% and the unit cell volume was not affected. Scanning electron microscopy (SEM) showed agglomeration of particles. Nanoparticle tracking analysis (NTA) results demonstrated that the use of SS produced the smallest particles (approximately 60nm).